(untitled) (MAUSAM, 1996)
ABSTRACT. The parameters controlling water requirement of wheat and its crop data, at various critical growth stages from ten different agroclimatic zones for five years. were collected and analysed. The study revealed that the total CU-demand for wheat crop in different wheat growing zones varied from 160 to 465 mm of water. In most of the zones, peak CU-demand were either at milk stage (21.0% of the total CU demand or at different stages (19.5% of the total CU-demand). Rabi season rainfall was not sufficient to meet the crop C.U-demand at different growth stages. The soil moisture study revealed that its depletion started around tillering stage indicating thereby, need for irrigation water beyond that stale. Computed average Kc, values (throughout the crop growth period) varied from 0.36 to 1.05 in different agroclimatic zones. Growth stage-wise K, values at or after elongation stage even exceeded one. Wheat yield in various agroclimatic zone varied from 1900 to 4800 kg/ha with the average productivity of 17 to 26 kg/ha/day. The WUE of the crop in different zones lay between 5 to 17 kg of grain/ha/mm of water. Depending upon this study wheat growing areas were divided into six zones.